Drp1-mediated mitochondrial fission regulates calcium and F-actin dynamics during wound healing - Ponte, Susana (2020)
This work was supported by national funds through FCT - Fundação para a Ciência e a Tecnologia, I.P., in the context of a program contract to L. Carvalho (4, 5 and 6 of article 23.º of D.L. no. 57/2016 of 29 August, as amended by Law no. 57/2017 of 19 July), PD/BD/106058/2015 to S. Ponte and PTDC/BIA-BID/29709/2017; the European Research Council (2007-StG-208631) and CONGENTO LISBOA-01-0145-FEDER-022170.